Efficiency of Orthopaedic Brace with Laser on Knee Joint Function, Pain and Swelling (Baltic Journal of Sport and Health Sciences, 2015)
Background. The effectiveness of outpatient mobile laser intervention on specific treatment goals has not been fully explored. Thus, the aim of the study was to examine the effect of orthopaedic knee brace with laser on knee joint function, pain and swelling.Methods. Volunteers were divided into two experimental groups: chronic pain (n = 20, knee pain > 6 months) and acute pain (n = 20, knee pain < 1 week), and one control (n = 20, placebo) group. Subjects in all groups were immobilized in a knee brace for 4 weeks. In addition, the experimental groups underwent low-intensity laser therapy, whereas control group underwent pseudo-laser therapy, every second day for 10 min. The sequences of the tests were as follows: (a) clinical assessments and evaluation of knee extension and flexion amplitude, swelling, Lysholm subjective assessment questionnaire, VAS pain scale, (b) evaluation of balance using Kistler platform, (c) muscle peak torque and isometric torque variability assessment using isokinetic dynamometry. All tests were performed twice - before and after intervention.Results. Knee brace with laser is effective treatment for the reduction of pain, swelling, and recovering of daily functions (p < .05). Operation of the complex device is particularly effective in treating knee pain in the acute period (p < .05).Conclusions.  Knee  brace  with  laser  therapy  in  the  rehabilitation  period  ensures  faster  healing  of  patients compared to wearing only knee brace, particularly in acute pain, while muscle strength and proprioception remains depressed.Keywords:  mobile laser therapy, range of motion, swelling, muscle strength, proprioception.